Burning fat: role of polyphenols in white adipose tissue browning - Perdicaro, Diahann Jeanette (2020)
Obesity is one of the main public health concerns worldwide. White adipose tissue (WAT) is an endocrine organ that stores energy excess as triglycerides. Increased adiposity, mainly visceral WAT, is strongly associated with insulin resistance, type 2 diabetes and cardiovascular disease, among others. In contrast to WAT, brown adipose tissue (BAT) has the ability to dissipate energy in the form of heat due to the presence of the uncoupling protein 1 (UCP-1), a key determinant of mitochondrial thermogenesis. Interestingly, ?brown-like? adipocytes can be observed in WAT and are characterized by the presence of multilocular lipid droplets and high number of mitochondria which are associated with a reduction of total adiposity and improvement of metabolic alterations. WAT browning can be triggered by different stimuli such as cold, exercise or pharmacological treatment, such as β-adrenergic stimulation or peroxisome proliferator-activated receptor-γ (PPARγ) agonists. In addition, bioactive compounds such as polyphenols had been recently implicated in the emergence of brown-like cells in WAT. Polyphenols are bioactive compounds widely distributed in fruits and vegetables with an important role in preventing and managing increased adiposity and its comorbidities. We observed in rodent models of high fat-induced increased adiposity and metabolic alterations that supplementation with grape pomace extract (GPE), rich in polyphenols, stimulate the expression of the main transcriptional regulators of brown-like cell development, i.e., PPARγ-coactivator-1α (PGC-1α), PPARγ, PR domain containing 16 (PRDM16), and UCP-1 reducing adipose hypertrophy and inflammation in WAT and insulin resistance. GPE and two of the major GPE flavonoids, quercetin and (-)-epicatechin, enhanced the expression of transcriptional regulators of browning and UCP-1 through the up-regulation of the β-adrenergic receptor downstream cascade in 3T3-L1 adipocytes treated with palmitate. Overall, this finding highlights the potential utilization of bioactive grape-derived compounds to prevent/attenuate adiposity-associated pathologies.